Shape and diameter of soil aggregates as sources of variation in tensile strength - Oliveira, Lucas de Sousa; Queiroz, Alexandre dos Santos; Lopes, Angélica da Silva; Silva, Francisca Gleiciane da; Mota, Jaedson Cláudio Anunciato (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Soil quality is essential to ensure the sustainability of agro-ecosystems. Tensile strength is one of the indicators frequently used for monitoring soil quality, being influenced by several factors, such as the size and shape of the aggregate. In this research, the hypothesis that the use of a single form of soil aggregates reduces the variability in the evaluation of the structural quality of soils was considered. In addition, the size of the aggregates influences the determination of tensile strength. Thus, the objective was to evaluate the relationship of tensile strength with the size and shapes that aggregates can assume. Two aggregate diameter bands (25-19 and 19-7.96 mm) and three aggregate forms (irregular, planed and spherical bases) were used. The aggregates with smaller diameters (13.5 mm) presented the highest mean values of tensile strength (82.73 kPa). The tensile strength determined in spherical aggregates showed less variability. For these aggregates, the coefficient of variation of the tensile strength was 29.30 and 19.29%, for the average diameters of 22 and 13.5 mm, respectively. As a result, shape must be considered when assessing the tensile strength of the soil aggregate.